Prevalence and correlates of vitamin D deficiency in adults after traumatic brain injury. (28th March 2016) - Jamall, Omer A.; Feeney, Claire; Zaw‐Linn, Joanna; Malik, Aysha; Niemi, Mari E.K.; Tenorio‐Jimenez, Carmen; Ham, Timothy E.; Jilka, Sagar R.; Jenkins, Peter O.; Scott, Gregory; Li, Lucia M.; Gorgoraptis, Nikolaos; et al.
Summary: Objectives: Traumatic brain injury (TBI) is a major cause of long‐term disability with variable recovery. Preclinical studies suggest that vitamin D status influences the recovery after TBI. However, there is no published clinical data on links between vitamin D status and TBI outcomes. The aim was to determine the (i) prevalence of vitamin D deficiency/insufficiency, and associations of vitamin D status with (ii) demographic factors and TBI severity, and with (iii) cognitive function, symptoms and quality of life, in adults after TBI. Design: Retrospective audit of patients seen between July 2009 and March 2015. Serum vitamin D (25‐hydroxy‐cholecalciferol) was categorized as deficient (<40 nmol/l), insufficient (40–70 nmol/l) or replete (>70 nmol/l). Patients: A total of 353 adults seen in tertiary hospital clinic (75·4% lighter skinned, 74·8% male, age median 35·1 year, range 26·6–48·3 year), 0·3–56·5 months after TBI (74·5% moderate–severe). Measurements: Serum vitamin D concentrations; Addenbrooke's Cognitive Examination (ACE‐R), Beck Depression Inventory‐II (BDI‐II), SF‐36 Quality of Life, Pittsburgh Sleep Quality Index. Results: In total, 46·5% of patients after TBI had vitamin D deficiency and 80·2% insufficiency/deficiency. Patients with vitamin D deficiency had lower ACE‐R scores than those of vitamin D replete (mean effect size ± SEM 4·5 ± 2·1, P = 0·034), and higher BDI‐II scores than those of vitamin D insufficient (4·5 ± 1·6, P = 0·003), correcting for age, gender, time since TBI and TBI severity. There was no association between vitamin D status and markers of TBI severity, sleep or quality of life. Conclusion: Vitamin D deficiency is common in patients after TBI and associated with impaired cognitive function and more severe depressive symptoms.